2014
DOI: 10.4172/2157-7110.1000344
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in Food Products: A Review

Abstract: Acrylamide or 2-propenamide an industrial chemical formed in some foods particularly starchy foods during heating process such as baking, frying and roasting. Acrylamide is proven to be carcinogenic in animals and a probable human carcinogen mainly formed in foods by the reaction of asparagine (free amino acid) with reducing sugars (glucose and fructose) as part of the Maillard reaction during heating under high temperature and low moisture conditions. The main aim of this review is to summarize the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 148 publications
(154 reference statements)
1
30
0
1
Order By: Relevance
“…[20][21][22][23] In addition electric fields can also lower fouling through electrophoresis or electrolysis of water. [11][12][13][14][15] Reduction of the powder particles size is possible, as micro-powders of different polymers are commercially available and will lead to a smaller pore size, thinner membranes and, therefore, for microfiltration applications in different ranges. This research showed a simple, cost-effective way to produce permeable, electrically conductive structures from nanocomposite powder particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] In addition electric fields can also lower fouling through electrophoresis or electrolysis of water. [11][12][13][14][15] Reduction of the powder particles size is possible, as micro-powders of different polymers are commercially available and will lead to a smaller pore size, thinner membranes and, therefore, for microfiltration applications in different ranges. This research showed a simple, cost-effective way to produce permeable, electrically conductive structures from nanocomposite powder particles.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst other approaches, an electrical field is applied to enhance flux and reduce the fouling process in electrofiltration through electrophoresis and electro-osmosis. [11][12][13][14][15] In many cases, an electrically nonconductive membrane on a support structure is mounted in front of an electrical cathode to repel and move negatively charged particles and molecules. [16,17] Electrically conductive membranes are an interesting option to function as cathode and, therefore, allow for simpler and more compact membrane module constructions.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of acrolein and acrylic acid through the dehydration of fats when heated at high temperature has been proposed as another mechanism of ACR formation [6,14]. The studies of Becalski et al [19] also indicated that ACR can be formed along with ammonia from Figure 2.…”
Section: Formation Of Acrylamidementioning
confidence: 83%
“…For over a decade since its discovery, several studies have been published in the literature on its formation, presence in various food products and toxicity in different parts of the world [1,[4][5][6]. In contrast, there is a dearth of information on its incidence and prevalence in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of water also plays a role in acrylamide formation. [12] When the food is cooked at very high temperatures, it tends to lose its moisture content. The moisture content between 0.4 to 0.7 is the range where there is acrylamide activity observed.…”
Section: Effect Of Ph Water and Fermentation On The Acrylamide Contentmentioning
confidence: 99%